The financial support for long-term elderly care and household saving behaviour - Asako Ohinata; Matteo Picchio (Global Labor Organization (GLO), 2017)
We analyse how the financial support for long-term elderly care affects the household's propensity to save. Using the difference-in-differences estimator, we investigate the 2002 Scottish reform, which introduced free formal personal care for all the Scottish elderly aged 65 and above. We find that the policy reduced the household saving rate by 1:9 percentage points. This amounts to an annual reduction in the flow of saving of 503. Moreover, the estimated effect is heterogeneous across the age of the head of household. The largest effect is observed when the household head is in his/her 40s, with the reduction in the saving rate of 3:5 percentage points or 1; 213 per year.
Keywords: C21; D14; I18; J14; 330; Long-term elderly care; ageing; means tested financial support; saving rate; difference-in-differences